PARTNERSHIP ORGANIZATIONAL MECHANISM IN RURAL AREAS DEVELOPMENT: STAKEHOLDERS ANALYSIS - ATKOČIŪNIENĖ Vilma; ŠTAREIKĖ Eglė (2017)
Process of rural areas development becoming more open and complex. lmpact of stakeholders is getting more elear and transparent for decisions and acts which are done in rural areas. Success and effectiveness of development initiatives ensuring stakeholder's goals that need to be linked with development purposes of rural organizations, which are implemented acting in partnership. Partnership organizational mechanism synchronizes actions and interactions of stakeholders and other elements of the mechanism, organizational changes and also combines interests of stakeholders and motivates them to engage and participate in rural development initiatives in order to solve existing problems. The purpose of this article - to define partnership organizational mechanism and determine stakeholders related with mechanism's functioning. During the investigation the evolution of the mechanism concept was analyzed, that created preconditions for creation of concept of partnership organizational mechanism in rural areas development. The missions analysis of Lithuania's 51 local action groups development strategies (2007-2013 year) allowed to identify stakeholders, that are related to partnership organizational mechanism functioning in rural areas development.